2009
DOI: 10.1017/s0143385709000042
|View full text |Cite
|
Sign up to set email alerts
|

The homoclinic and heteroclinic C*-algebras of a generalized one-dimensional solenoid

Abstract: D. Ruelle and I. Putnam have constructed three C*-algebras from the homoclinic and heteroclinic structure of a Smale space. This paper gives gives a complete description of these algebras when the Smale space is one of the generalized one-dimensional solenoids studied by R. Williams and I. Yi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…(We remark that this description of ρ is almost identical to that given in [Th5,Lemma 3.5] in a different setting.) Define p j : D j → A j such that p j (a, f ) = a, and note that p k+1 • is homotopic to (χ + µ • I k ) • p k so that…”
Section: Markov Mapssupporting
confidence: 70%
“…(We remark that this description of ρ is almost identical to that given in [Th5,Lemma 3.5] in a different setting.) Define p j : D j → A j such that p j (a, f ) = a, and note that p k+1 • is homotopic to (χ + µ • I k ) • p k so that…”
Section: Markov Mapssupporting
confidence: 70%
“…We illustrate the techniques for doing this in the example of the 'aab/ab-solenoid', a specific example of a Williams solenoid constructed from a certain map on a wedge sum of two circles. The reader should be aware that the K -theory of this example (and any one-dimensional Williams solenoid) is well known, see [33] (and also [24,25]). Our techniques are also applicable to any one-dimensional Williams solenoid.…”
Section: Theorem 12 (See Theorem 417)mentioning
confidence: 99%
“…Note that g is not a local homeomorphism in this example. For more details on this specific example and one-solenoids in general, see [25,28,33].…”
Section: Examples Of Wieler Solenoidsmentioning
confidence: 99%
“…It was shown by Williams that expanding attractors of certain diffeomorphisms of compact manifolds are one-solenoids via a conjugacy which turns the restriction of the diffeomorphism into f . He also showed that each one-solenoid arises in this way from a diffeomorphism of the 4-sphere [11].…”
Section: One-dimensional Generalized Solenoidsmentioning
confidence: 99%
“…Following Williams and Yi [15,17], Thomsen called (X, f ) a generalized one-dimensional solenoid or just a one-solenoid [11]. It was shown by Williams that expanding attractors of certain diffeomorphisms of compact manifolds are one-solenoids via a conjugacy which turns the restriction of the diffeomorphism into f .…”
Section: One-dimensional Generalized Solenoidsmentioning
confidence: 99%